Computed angiographic variations in hepatic venous vasculature in dogs - Satoshi, Takagi; Ayano, Nishino; Kiwamu, Hanazono; Kenji, Hosoya (Veterinary Surgery, 2022)
Objective To identify the number of hepatic veins draining directly or indirectly into the caudal vena cava Thank you (CVC) using computed tomography angiography (CTA) in dogs. Study design Retrospective clinical study. Animals Client‐owned dogs (n = 77). Methods Abdominal CTA images were analyzed. Retrospective convenience sampling was performed using archived clinical cases to determine the number of hepatic veins in each liver lobe. Results A median of 2 vessels from the right lateral lobe (range: 1‐4) and the caudate process of the caudate lobe (range: 1‐5) drained directly into the CVC. In the quadrate lobe, most common patterns consisted of 1 vessel directly draining to the CVC or indirectly via the left hepatic vein (LHV), and a vessel from quadrate lobe and right medial lobe merging into 1 vessel draining into the CVC or the LHV. A median of 3 vessels in the left lateral lobe (range: 2‐8) and a median of 1 vessel in the left medial lobe (range: 1‐3) drained into the LHV. In the papillary process of the caudate lobe, a median of 1 (range: 1‐2) vessel drained directly into the CVC or the LHV. Conclusion The draining pattern of hepatic veins varied widely in all liver lobes, especially the left lateral liver lobe. Clinical significance Veterinary surgeons should consider the potential presence of multiple hepatic veins and their draining pattern when performing hilar liver lobe resection. Attentive evaluation of a preoperative CTA is recommended for surgical planning.